Fast Neutron Fluence Rate Measurement for the Neutron Beams at IHNI-1 - WANG Gu-jun1;CHEN Jun1;LI Chun-juan1;SONG Ming-zhe1;ZHANG Zi-zhu2 (Journal of Isotopes, 2017)
To validate and determine the contamination source term of fast neutrons produced by the first in-Hospital Neutron Irradiator (IHNI-1) for boron neutron capture therapy (BNCT), a boron-covered 235U fission chamber was designed to be used for the measurement of fast neutron fluence rate. The fluence response of the fission chamber was optimized according to the calculated fluence response curve of the fission chamber covered by the boron shells with different thicknesses with the MCNP code. Consequently, a 35 mm thick B4C shell was used to shield the low energy neutrons. The fast neutron fluence rate of the thermal and epithermal neutron beams was measured with the fission chamber and compared with the simulated values. The results showed that the fast neutron component in the actual neutron beams was more than that in the simulated ones, less than the target value recommended by IAEA.